2013
DOI: 10.31989/ffhd.v3i9.42
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Anti Helicobacter pylori and antioxidant effects of Artemisia Judaica

Abstract: Artemisia judaica (AJ) is one of the common species of the genus Artemisia that grows in Saudi Arabia desert and Sinai, Egypt where animals graze on it. It is widely used in traditional medicine and by Bedouins there. (AJ) has anthelmintic, antibacterial, antiinflammatory, analgesic and antipyretic effects. The present study aimed to (1) elucidates the antibacterial action of AJ against H. pylori and different other bacterial species (2) delineate the potential antibacterial mechanism of action of AJ in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…The natural antioxidants act as a shelter against the offensives of free radicals that can induce harms to the cell [33]. A. judaica, one of the widespread species of the genus Artemisia, is a desert medicinal plant usually used as tea by population in Egypt Sinai [34]. In the traditional medicine of the Arabic area; A. judaica was used to treat skin disorders, weak immune system and gastrointestinal disorders and also to decrease the risk of cancer [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The natural antioxidants act as a shelter against the offensives of free radicals that can induce harms to the cell [33]. A. judaica, one of the widespread species of the genus Artemisia, is a desert medicinal plant usually used as tea by population in Egypt Sinai [34]. In the traditional medicine of the Arabic area; A. judaica was used to treat skin disorders, weak immune system and gastrointestinal disorders and also to decrease the risk of cancer [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in other traditional medicines of the Arabic region, A. judaica is also used to treat gastrointestinal disorders, and to enhance eyesight, for cardiovascular health, capillary strength and improving the structure of connective tissue, appearance of skin, and the immune system, while promoting decreased risk of atherosclerosis, cancer and arthritis (Khafagy et al, 1988;Janaćković et al, 2015). Furthermore, it is reported that A. judaica has been used in traditional medicine of Bedouins in the Saudi Arabia desert and Sinai, Egypt as a herbal remedy with anthelmintic, antibacterial, anti-inflammatory, and analgesic activities (El-Sayed et al, 2013). It also relieves snake stings, scorpion bites, ear infections, dysentery, coughing and external wounding (Friedjung, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Also, water extract of A. judaica sourced from Saudi Arabia showed stronger antioxidant action than trolox (El-Sayed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia judaica L. (‘shih balady’ in Arabic), considered a herbal medicine in Egypt, is characterized by the presence of comparatively high percentages of piperitone and camphor . Anti‐inflammatory, antioxidant, antimicrobial, anti‐helicobacter, anti‐helmintic, anti‐pyretic, and analgesic properties have been reported for EOs derived from A. judaica . Artemisia monosperma is widespread in desert plains and wadis, and its leaves are widely used in Egypt and Saudi Arabia in folk medicine .…”
Section: Introductionmentioning
confidence: 99%
“…12 Anti-inflammatory, antioxidant, antimicrobial, anti-helicobacter, anti-helmintic, anti-pyretic, and analgesic properties have been reported for EOs derived from A. judaica. [12][13][14][15][16] Artemisia monosperma is widespread in desert plains and wadis, and its leaves are widely used in Egypt and Saudi Arabia in folk medicine. 2 It demonstrates antibacterial activity against Streptococcus agalactiae with a stronger inhibition than recorded for ampicillin.…”
Section: Introductionmentioning
confidence: 99%